2016
DOI: 10.5966/sctm.2015-0166
|View full text |Cite
|
Sign up to set email alerts
|

Priming Dental Pulp Stem Cells With Fibroblast Growth Factor-2 Increases Angiogenesis of Implanted Tissue-Engineered Constructs Through Hepatocyte Growth Factor and Vascular Endothelial Growth Factor Secretion

Abstract: Tissue engineering strategies based on implanting cellularized biomaterials are promising therapeutic approaches for the reconstruction of large tissue defects. A major hurdle for the reliable establishment of such therapeutic approaches is the lack of rapid blood perfusion of the tissue construct to provide oxygen and nutrients. Numerous sources of mesenchymal stem cells (MSCs) displaying angiogenic potential have been characterized in the past years, including the adult dental pulp. Establishment of efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 64 publications
1
83
0
3
Order By: Relevance
“…It is well known that specific conditions of the microenvironment, like hypoxia, can induce the upregulation of stem cell mediated angiogenesis (17, 18). It has more recently been shown that not only can hypoxia induce expression of VEGF specifically from DPSCs (19), but that FGF-2 can directly upregulate VEGF and HGF secretion from pulp cells of deciduous teeth (SHEDs) (20). Through similar mechanisms to FGF-2, there could be components of the human sera which induce or upregulate the production of specific angiogenic proteins from DPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that specific conditions of the microenvironment, like hypoxia, can induce the upregulation of stem cell mediated angiogenesis (17, 18). It has more recently been shown that not only can hypoxia induce expression of VEGF specifically from DPSCs (19), but that FGF-2 can directly upregulate VEGF and HGF secretion from pulp cells of deciduous teeth (SHEDs) (20). Through similar mechanisms to FGF-2, there could be components of the human sera which induce or upregulate the production of specific angiogenic proteins from DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have used various models to investigate the in vivo angiogenic capacity of pulp-derived stem cells from both primary (SHEDs) and adult (DPSCs) teeth and it is clear that they maintain strong angiogenic potential following transplantation (4, 2023). Through co-transplantation with endothelial cells or transplantation alone, these cells have been shown to induce angiogenesis attributed primarily to their release of trophic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial shift of MSCs in these studies is mainly indicated by the upregulation of typical endothelial cell (EC) markers, such as PECAM-1, VEGFR-2, vWF, and VE-cadherin and further evidenced by functional assays, such as ability to form capillary-like structures on Matrigel or other matrices or by uptake of Acetylated-Low Density LipoProtein Lipase (Ac-LPL), but also by various in vivo assays, including mouse Matrigel assays and Chicken Chorioallantoic Membrane (CAM) assays [33, 34, 122]. …”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…Dental and craniofacial research currently explores a variety of cell-based and tissue engineering protocols to be used as alternatives to classical therapies that aimed at repairing/regenerating damaged tissues (Ducret et al, 2015a; Gorin et al, 2016). In particular, studies have demonstrated that mesenchymal stromal/stem cells (MSCs) are suitable to these protocols because of their high expansion ability and differentiation potential both in culture and animal models.…”
Section: Introductionmentioning
confidence: 99%